Application of Insect Growth Regulators (IGRs) as Biopesticides for Sustainable Agriculture (International Journal of Scientific Research in Science and Technology, 2024)
The application of conventional pesticides is underlined by many negative externalities including environmental degradation and pest resistance. Consequently, use of biopesticides as alternative agrochemicals is recommended to meet sustainable development goals. Insect growth regulators (IGRs) are biochemical biopesticides. Actually, Biochemical biopesticides are compounds (or exact synthetic analogue) of natural origin possessing active ingredients that control pest in a way that are nontoxic to the target pest, the environment and humans. So, insecticides with growth regulating properties may adversely affect insects by regulating or inhibiting specific biochemical pathways or processes essential for insect growth and development. Ecdysoids and Juvenoids (JH mimics) are among the most promising IGRs. Ecdysoids are synthetic analogues of natural ecdysone and when applied in insects, kill them by formation of defective cuticle. Juvenoids (JH mimics) are synthetic analogues of Juvenile Hormone (JH). Juvenoids have anti-metamorphic effect on immature stages of insect. Along with this, Anti JH or precocenes which act by destroying corpora allata and preventing JH synthesis also act as IGR. In this way, Insect Growth Regulators are potential substitute of insecticides that could be commercially used.